SATISFACTION USERS OF LEVONORGESTREL IMPLANTS. EXPERIENCE CAYETANO HEREDIA NATIONAL HOSPITAL - Pretell Mazzini, Juan (2015)
OBJECTIVES. To determíne the characteristics and satisfaction of levonorgestrel users (Norplant®) at the CHNH Family Planning Program. DESIGN: Descriptive retrospective study. MATERIAL AND METHODS: Eighty-two users to whom Norplant® was removed between January 1995 and December 1999, were included. Data was obtained from records and satisfaction was evaluated through a survey employing Likert´scale. RESULTS: Up to 71,9% ofusers were satisfied, The pregnancy rate was 0%; 70,7% of users presented a side effect, being menstrual irregularíties the most frequent (47,6%). The main advantage was protection against pregnancy at the long term (53,7%). A 59% of continuity was registered during the five years and the main causes of early removal were pregnancy desire and menstrual alterations with 23,5% in both cases. A statistical significance was found with users satisfaction in the following variables: weight gain (p= 0,0077), pain at the implantation zone (p= 0,000055), depressive symptoms (p= 0,000000), educational level (p= 0, 033), method recommendation (p= 0, 0000) and desire for a re -implant (p= 0,00000). CONCLUSIONS. The levonorgestrel subdermal implants (Norplant®) was a very well accepted contraceptive method in spite of the side effects, high1y effective and a good alternative for women wishing a long term contraceptive.